2012
DOI: 10.1021/es202942q
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Deepwater Horizon Oil Spill on Bioavailable Polycyclic Aromatic Hydrocarbons in Gulf of Mexico Coastal Waters

Abstract: An estimated 4.1 million barrels of oil and 2.1 million gallons of dispersants were released into the Gulf of Mexico during the Deepwater Horizon oil spill. There is a continued need for information about the impacts and long-term effects of the disaster on the Gulf of Mexico. The objectives of this study were to assess bioavailable polycyclic aromatic hydrocarbons (PAHs) in the coastal waters of four Gulf Coast states that were impacted by the spill. For over a year, beginning in May 2010, passive sampling de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
208
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(222 citation statements)
references
References 38 publications
11
208
1
2
Order By: Relevance
“…This is in contrast to 96 h LC 50 PAH values, in which little difference in toxicity was seen for WAFs and CEWAFs. In the wake of the Deepwater Horizon event, reported concentrations of TPAHs in May 2010 varied greatly dependent on site and sampling depth and ranged from 0 to 146 mg L´1 at the wellhead, 0 to 0.9 mg L´1 in field collected WAFs, 0 to 18 mg L´1 in field collected CEWAFs, and 0 to 0.17 µg L´1 in shoreline samples [45][46][47]. Following capping of the well in July concentrations in collected sample were significantly lower at all sites and depths.…”
Section: Survivalmentioning
confidence: 99%
“…This is in contrast to 96 h LC 50 PAH values, in which little difference in toxicity was seen for WAFs and CEWAFs. In the wake of the Deepwater Horizon event, reported concentrations of TPAHs in May 2010 varied greatly dependent on site and sampling depth and ranged from 0 to 146 mg L´1 at the wellhead, 0 to 0.9 mg L´1 in field collected WAFs, 0 to 18 mg L´1 in field collected CEWAFs, and 0 to 0.17 µg L´1 in shoreline samples [45][46][47]. Following capping of the well in July concentrations in collected sample were significantly lower at all sites and depths.…”
Section: Survivalmentioning
confidence: 99%
“…The extent of the surface oil spill varied widely from day to day because of changes in wind patterns and ocean currents (Cleveland et al, 2010). The estimated amount of oil spilled was 4.1 million barrels of oil that contains around 2.1 × 10 10 of polycyclic aromatic hydrocarbons, which is a toxic material arming wildlife and humans (Allan, 2012). Smith et al (2011) estimated the economic impact of the event to be 36.9$ billion.…”
Section: Research Area and Materialsmentioning
confidence: 99%
“…Of course, oil spills are well-known examples of PAH contamination in the aquatic environment. Unfortunately, many cases of studies are reported in the literature from different parts of the world, such as the Gulf of Mexico in [94], the Mediterranean Sea [95], the Spanish coasts [96], and the Philippines islands [97].…”
Section: Environmental Monitoring Of Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%